Guidelines for the Treatment of Malaria. - Organization, World Health (Nonseral Publication., 2010)
Malaria control requires an integrated approach, including prevention (primarily vector control) and prompt treatment with effective antimalarials. Since the publication of the first edition of these Guidelinesin 2006, most of the countries where P. Falciparum is endemic have progressively updated treatment policies from the failing chloroquine and sulphadoxine-pyrimethamine to the recommended artemisinin-based combination therapies (ACTs); this is the best current treatment for uncomplicated falciparum malaria. Unfortunately, the implementation of these policies has lagged behind due to vario.